Adaptation to beach erosion at Maremma Regional Park (Tuscany, Italy) (Geo-Eco-Marina, 2013)
Severe erosion has been affecting the Ombrone river delta apex since the second half of the 19th Century and is currently expanding gradually to adjacent beaches. Main causes of this process include coastal marsh reclamation, land-use changes within the watershed, dam construction, and river bed quarrying. In addition, the Ombrone river delta area is subsiding at an average rate of approximately 10 mm/yr. As a result, the river mouth underwent shoreline retreat of over 1100 m in the past 130 years, and the erosion rate currently reaches a peak of 10 m/yr. During recent decades, the Maremma Regional Park decided to allow for beach erosion to proceed, and therefore not to build shore protection structures along the coast. This aimed at keeping the natural landscape unaltered whereas preventing triggering beach erosion on neighboring coastal sectors fed by sediments eroded from the delta apex. However, due to recent acceleration in erosion rates, the shoreline now cuts the coastal dune system and salt water stems interdune swales during storms; as a consequence, valuable junipers, pine forests and freshwater ecosystems have been seriously damaged. In face of that, the Park administration applied for a sustainable shore protection project within the scope of the Regional Coastal Protection Plan, which consisted of managed realignment of 150 m shore extension. The existing, obsolete 420 m long dyke, presently located along the shoreline of the delta southern wing, will be removed and reconstructed 150 m inland as a major protection measure against extreme storm events. From the offshore side of the new seawall a set of 18 groins will be buried into the ground with the crest at –0.50 m; these structures will reach the present shoreline underground; six of them, in the southern sector, will be extended in the nearshore as submerged groins for approximately 150 m. Beach erosion will gradually exhume these structures, which will become progressively more effective in reducing current shoreline retreat rates. Shoreline is forecasted to reach the seawall within 15 to 25 years in such protected conditions. In the meantime the Ombrone River Basin Authority will have to implement efficient measures for restoring river sediment transport at a magnitude capable of allowing natural beach stabilization in the littoral cell. If these parallel actions are developed in the near future, shoreline retreat will be halted before the seawall is reached, resulting in a sandy beach stabilized by the submerged groin set.
Keywords: river delta; natural park; coastal erosion; shore protection; managed realignment; submerged groins